2016
DOI: 10.11604/pamj.2016.24.294.8728
|View full text |Cite
|
Sign up to set email alerts
|

Triage capabilities of medical trainees in Ghana using the South African triage scale: an opportunity to improve emergency care

Abstract: IntroductionThe incidence of emergency conditions is increasing worldwide, particularly in low- and middle-income countries (LMICs). However, triage and emergency care training has not been prioritized in LMICs. We aimed to assess the reliability and validity of the South African Triage Scale (SATS) when used by providers not specifically trained in SATS, as well as to compare triage capabilities between senior medical students and senior house officers to examine the effectiveness of our curriculum for house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In comparison to Mbour, several other African countries are moving towards using the South African Triage Scale (SATS), which has been found to be an adaptable triage protocol in LMICs [20] . SATS does not rely on computer-based medical records, and has been found to be successful in low resource settings when users are properly trained [21] .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to Mbour, several other African countries are moving towards using the South African Triage Scale (SATS), which has been found to be an adaptable triage protocol in LMICs [20] . SATS does not rely on computer-based medical records, and has been found to be successful in low resource settings when users are properly trained [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Two articles assessing reliability in South Africa report moderate to substantial reliability with QWK of 0.57 and 0.66, respectively. 14 15 In Ghana, the SATS showed moderate reliability with QWK of 0.59 and 0.60 16 while studies in Pakistan and Botswana reported substantial to near-perfect results with QWK of 0.77 and 0.87, respectively. 8 9 In high-resource settings, the Canadian Emergency Department Triage and Acuity Scale (CTAS), a 5-level triage scale, reported a chance corrected kappa of 0.80 and a weighted kappa of 0.77.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, low-and middle-income community hospitals should implement a systematic triage system to insure their limited human and physical emergency resource capacity is being utilized for appropriate patients, which can help decrease the time a critical patient is waiting to be treated by provider. The South African Triage Scale (SATS), developed in 2004, has proven to be a reliable and validated tool that has been implemented in various western African countries, including Ghana [15]. The SATS divides patients into five different urgency categories based on a brief clinical assessment of a patient, with each category indicating how quickly a physician should see them [16].…”
Section: Discussionmentioning
confidence: 99%
“…The SATS divides patients into five different urgency categories based on a brief clinical assessment of a patient, with each category indicating how quickly a physician should see them [16]. Implementation of SATS, along with training in EM, has shown to reduce wasting of medical resources and reduce morbidity and mortality in patients [15]. This study was not without limitations.…”
Section: Discussionmentioning
confidence: 99%